Detection of cardiac involvement in pulmonary sarcoidosis using high‐resolution Holter electrocardiogram. Issue 2 (12th January 2021) - Maru, Yujin; Yodogawa, Kenji; Tanaka, Toru; Kashiwada, Takeru; Iwasaki, Yu‐ki; Azuma, Arata; Shimizu, Wataru
Abstract: Background: Early detection of cardiac involvement in patients with sarcoidosis is important but currently unresolved. The aim of this study was to elucidate the utility of frequency domain microvolt T‐wave alternans (TWA), signal‐averaged ECG (SAECG), and heart rate turbulence (HRT) using 24‐hour Holter ECG for detecting cardiac involvement in patients with pulmonary sarcoidosis. Methods: This study consisted of consecutive 40 pulmonary sarcoidosis patients (11 males, 62 ± 13 years) who underwent 24‐hour Holter monitoring with and without cardiac involvement. All patients underwent frequency domain TWA, SAECG, and HRT using 24‐hour Holter monitoring. Patients with atrial fibrillation pacing or wide QRS electrocardiogram were excluded. Results: After 14 patients were excluded, a total of 26 patients (six males, 59 ± 14 years) were evaluated. Seven patients had cardiac involvement (cardiac sarcoidosis [CS] group). On the Holter SAECG, duration of low‐amplitude signals <40 μV in the terminal filtered QRS complex (LAS40) was significantly higher, and root mean square voltage of the terminal 40 ms of the filtered QRS complex (RMS40) was significantly lower in the CS group compared with the non‐CS group (LAS40: 61.4 ± 35.9 vs 37.6 ± 9.2 ms; P = .018, RMS40: 11.4 ± 10.3 vs 23.6 ± 13.2 ms; P = .023). Prevalence of positive late potential (LP) was also significantly higher in the CS group than that in the non‐CS group (85.7% vs 31.5%; P = .026). The sensitivity, specificity, positive, and negative predictive values of LP for identifying patients with cardiac involvement were 85.7%, 68.4%, 50.0%, and 92.8%, respectively. Conclusion: Holter SAECG may be useful for detecting cardiac involvement in patients with pulmonary sarcoidosis. Abstract : Holter‐based signal‐averaged ECG showed high prevalence of positive late potentials (LP) in cardiac sarcoidosis (CS) patients.